UTILIZING PODCAST TO IMPROVE INFORMATICS MANAGEMENT STUDENTS’ LISTENING COMPREHENSION AND PARTICIPATION AT AMIK MITRA GAMA - Eka Melati Eka Melati; Yessi Ratna Sari; Syamsiah Depalina Siregar (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
Technology of podcasting becomes a popular teaching media in education nowadays. It gives the students opportunity to study anytime and anywhere. It is flexible, dynamics and powerful to improve students listening comprehension. It gives new challenge in the context of language learning especially listening that as first skill of language acquisition. This was a classroom action research study. It aims at identifying the listening improvement of third semester students of Informatics Management at AMIK Mitra Gama academic year 2019/2020 by using podcasts. The participants were 24 students(3 MMI class). Finding of this study showed that utilizing podcast can improve not only student’s listening comprehension achievement (66.96% in fisrt cycle to 68,29% in second cycle) but also student’s participation (46,67% in cycle 1 to 56,67% in cycle 2). In sum, podcasts can be an attractive media in teaching listening at AMIK Mitra Gama.